2020
DOI: 10.1111/ijlh.13336
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of D‐dimer with severity and mortality in SARS‐CoV‐2 patients : A meta‐analysis

Abstract: Introduction The novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has caused a pandemic. Many studies have shown that several laboratory parameters are related to disease severity and mortality in SARS‐CoV‐2 cases. This meta‐analysis aimed to determine the relationship of a prognostic factor, D‐dimer, with disease severity, need for intensive care unit (ICU) care, and mortality in SARS‐CoV‐2 patients. Methods A systematic search for all observational studies and trials involving adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
5
28
0
3
Order By: Relevance
“…Although the molecular mechanisms underlying the hypercoagulable state described in COVID-19 patients are still incompletely understood (with endotheliopathy, due to the direct endothelial infection with SARS-CoV-2 and the indirect damage caused by inflammation, playing a predominant role) [29], multiple studies, reviews and meta-analyses have reported higher D-dimer levels to be associated with poorer outcomes and may even help predict these outcomes [6][7][8][9][10][11]. However, this potential role is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the molecular mechanisms underlying the hypercoagulable state described in COVID-19 patients are still incompletely understood (with endotheliopathy, due to the direct endothelial infection with SARS-CoV-2 and the indirect damage caused by inflammation, playing a predominant role) [29], multiple studies, reviews and meta-analyses have reported higher D-dimer levels to be associated with poorer outcomes and may even help predict these outcomes [6][7][8][9][10][11]. However, this potential role is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulopathy most commonly manifests as a pro-thrombotic state with increased incidence of both venous and arterial thrombosis [5]. Elevated D-dimer levels have consistently been shown as an important feature of severe COVID-19 patients [6][7][8][9][10][11]. Therefore, the International Society on Thrombosis and Haemostasis (ISTH) has recommended measuring D-dimer upon admission in all patients who present with COVID-19 [12].…”
Section: Introductionmentioning
confidence: 99%
“…As worthily described by the authors Mcfadyen and Goshua, the reduction of platelet count may be the sentinel of the viral infection that signals endotheliopathy, leukocytes activation and the thrombo‐inflammation state in COVID‐19 patients 21,24 . According to these outcomes, an early treatment of infected patients would be desirable, perhaps based on antithrombotic drugs, according to increasing evidence on the involvement of coagulation from the beginning of the viral infection 25,26 . Importantly, the pharmacological effects of anti‐inflammatory and antiplatelets drugs will be determined by controlled clinical trials currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, numerous review and meta-analyses highlighted the prognostic value of D-dimer in COVID-19 mortality ( 14 16 ). However, one of the drawbacks of these analyses was that more attention was paid to D-dimer levels between survivors and non-survivors ( 17 , 18 ). Actually, the abnormal elevation of D-dimer was more valuable to reflect hemodynamic changes in clinic.…”
Section: Introductionmentioning
confidence: 99%